Fictive Worlds and ‘Real’ Worlds: The Staging and Reception of Unreliable Narration in Hollywood Cinema (KULT_online, 2010)
Eva Laass' English-language dissertation investigates the staging and reception of 'unreliable narration' in film, using examples of popular Hollywood productions from the last two decades. The study was published as the third volume in the series WVT-Handbücher und Studien zur Medienkulturwissenschaft (WVT-Handbooks and Studies in Media Culture), edited by Knut Hickethier and Ansgar Nünning. Based on theoretical concepts of cognitive and intermedial narratology, the author develops a typology to describe and categorise unreliable filmic narration, which is applied and tested in close readings of films such as Forrest Gump (1994), Fight Club (1999), The Usual Suspects (1995), and Memento (2000). Consistently considering the viewer’s role as an active participant turns out to be a productive strategy in the course of her argument. The study closes with an investigation of the social dimension of unreliable narration which locates it within the specific sociopolitical context of Hollywood cinema.